Principles of epilepsy management in Pediatrics - Caridad Hernández Gutiérrez; Carmen E. Guerra Cabrera; Elodia Rivas Alpizar; Inti Santana Carballosa; Teresita Rodríguez Izaguirre (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
-